The Tocquevillian Historical Sociology as a Critical Perspective - Arens, Nicolas (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
This contribution aims to analyse how at the beginning of the historical sociology lies, already for precursors from the XIX century, a critical perspective. Alexis de Tocqueville (1805-1859) is one of the founders of this approach. His uses of the long-term perspective as well as of the European scope enable him to qualify critically the French Revolution. This paper argues that the Old Regime and the Revolution (Tocqueville 1856) presents the French revolution neither as a real Revolution, since it is an on-going process of the longue durée, nor as a French event, since it is a European one. This significance allows then to relate Tocqueville’s thought with “critical cosmopolitanism” (Delanty 2006) since the nineteenth-century author was trying to associate both the universal movement of equalization and the definition of an open political community.